2022
DOI: 10.3389/fneur.2022.883927
|View full text |Cite
|
Sign up to set email alerts
|

Immune–Inflammatory Biomarkers Predict Cognition and Social Functioning in Patients With Type 2 Diabetes Mellitus, Major Depressive Disorder, Bipolar Disorder, and Schizophrenia: A 1-Year Follow-Up Study

Abstract: BackgroundSystemic, low-grade immune–inflammatory activity, together with social and neurocognitive performance deficits are a transdiagnostic trait of people suffering from type 2 diabetes mellitus (T2DM) and severe mental illnesses (SMIs), such as schizophrenia (SZ), major depressive disorder (MDD), and bipolar disorder (BD). We aimed to determine if immune–inflammatory mediators were significantly altered in people with SMIs or T2DM compared with healthy controls (HC) and whether these biomarkers could help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…BD manic patients showed significantly higher TNF-α levels than controls at admission ( Kim et al, 2007 ; Junior et al, 2023 ; Polat et al, 2023 ), without receiving pharmacotherapy 2 ( Pandey et al, 2015 ) or 3 weeks before protein measurement ( Ortiz-Domínguez et al, 2007 ), when following stable treatment ( O'Brien et al, 2006 ; Kim et al, 2007 ; Kapczinski et al, 2011 ; Luo et al, 2016 ; Wang et al, 2016 ; Hoseth et al, 2017 ; Koga et al, 2019 ; Bavaresco et al, 2020 ; Zazula et al, 2022 ; Lu et al, 2023 ; Gong et al, 2022 ), and in both early ( Skibinska et al, 2022 ) and late BD stages ( Kauer-Sant Anna et al, 2009 ; Tatay-Manteiga et al, 2017 ), or significantly reduced levels in euthymic late patients but not in early BD patients ( Panizzutti et al, 2015 ). In other cases, no difference was found between controls and BD patients who were under medication ( Barbosa et al, 2011 ; Palacio et al, 2016 ; Doğanavşargil Baysal et al, 2019 ; Garés-Caballer et al, 2022 ; Jiang et al, 2022 ) with valproic acid monotherapy ( Chou et al, 2016 ) or at baseline when specified that BD patients had a manic episode ( Li et al, 2015 ; Jacoby et al, 2016 ) or were in their first episode ( Chen MH et al, 2020 ). During euthymia, TNF-α has also been unaltered compared to controls ( Kunz et al, 2011 ; Barbosa et al, 2012a ; Doganavsargil-Baysal et al, 2013 ; Wieck et al, 2014 ; Jacoby et al, 2016 ; Doğanavşargil Baysal et al, 2019 ; Millett et al, 2020 ; Vares et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…BD manic patients showed significantly higher TNF-α levels than controls at admission ( Kim et al, 2007 ; Junior et al, 2023 ; Polat et al, 2023 ), without receiving pharmacotherapy 2 ( Pandey et al, 2015 ) or 3 weeks before protein measurement ( Ortiz-Domínguez et al, 2007 ), when following stable treatment ( O'Brien et al, 2006 ; Kim et al, 2007 ; Kapczinski et al, 2011 ; Luo et al, 2016 ; Wang et al, 2016 ; Hoseth et al, 2017 ; Koga et al, 2019 ; Bavaresco et al, 2020 ; Zazula et al, 2022 ; Lu et al, 2023 ; Gong et al, 2022 ), and in both early ( Skibinska et al, 2022 ) and late BD stages ( Kauer-Sant Anna et al, 2009 ; Tatay-Manteiga et al, 2017 ), or significantly reduced levels in euthymic late patients but not in early BD patients ( Panizzutti et al, 2015 ). In other cases, no difference was found between controls and BD patients who were under medication ( Barbosa et al, 2011 ; Palacio et al, 2016 ; Doğanavşargil Baysal et al, 2019 ; Garés-Caballer et al, 2022 ; Jiang et al, 2022 ) with valproic acid monotherapy ( Chou et al, 2016 ) or at baseline when specified that BD patients had a manic episode ( Li et al, 2015 ; Jacoby et al, 2016 ) or were in their first episode ( Chen MH et al, 2020 ). During euthymia, TNF-α has also been unaltered compared to controls ( Kunz et al, 2011 ; Barbosa et al, 2012a ; Doganavsargil-Baysal et al, 2013 ; Wieck et al, 2014 ; Jacoby et al, 2016 ; Doğanavşargil Baysal et al, 2019 ; Millett et al, 2020 ; Vares et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a contribution of immune dysregulation to social-cognitive impairments in SZ patients is to be expected. Indeed, higher plasma levels of inflammatory components such as interleukin 10 (IL-10) predict social-functioning impairments [139]. Another study even found that higher IL-10 levels lead to misinterpretation of social cues and that elevated IL-2 correlates with other social-cognitive measures in SZ patients [140,141].…”
Section: Immune Dysregulation Is Associated With Social-cognitive Imp...mentioning
confidence: 99%